Improving Students’ Ability in Classroom Interaction through Everyone Is the Teacher Here - Kuswanti, Nunung (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2018)
This research is a case study that has been done in October until November 2013. The objective of this research was a group of students at seventh semester at Teacher Training and Education (STKIP) Muhammadiyah Sorong that was consists of five students. The aim of this research was to know whether ‘Everyone is Teacher Here’ is effective to improve students’ ability in classroom interaction.The design of this research was time series design that is equivalent time series design. The data of this research was analyzed through SPSS program that is Wilcoxon Test (nonparametric statistic). The steps of this research were: 1) selecting the participant 2) Measure for the first time 3) Giving the intervention 4) Measure for the second time 5) Giving the intervention 6) Measure for the third time 7) Giving the intervention 8) Measure for the fourth time. The data had gotten then analyzed. Based on the result of data analysis had gotten Asymp. Sig. (2-tailed) 0,0195 for the first and the second test, 0,0205 for the second and the third test and 0,017 for the third and the fourth test in which 0,0195, 0,0205 and 0,017 0,05, means that Ho was refused or Everyone is Teacher Here is effective to improve students’ ability in classroom interaction. In overall also got the result of the first and the fourth test with Asymp. Sig. (2-tailed) = 0,019 0,05, means that Ho was refused.